Biogeographical region and environmental conditions drive functional traits of estuarine fish assemblages worldwide. Issue 4 (24th January 2017) - Henriques, Sofia; Guilhaumon, François; Villéger, Sébastien; Amoroso, Sandra; França, Susana; Pasquaud, Stéphanie; Cabral, Henrique N; Vasconcelos, Rita P
Abstract: Assessing trait–environment relationships is crucial for predicting effects of natural and human‐induced environmental change on biota. We compiled a global database of fish assemblages in estuaries, functional traits of fishes and ecosystem features of estuaries. And we quantified the relative importance of ecosystem features as drivers of patterns of fish functional traits among estuaries worldwide (i.e. drivers of the proportions of fish traits). In addition to biogeographical context, two main environmental gradients regulate traits patterns: firstly temperature, and secondly estuary size and hydrological connectivity of the estuary with the marine ecosystem. Overall, estuaries in colder regions, with larger areas and with higher hydrological connectivity with the marine ecosystem, have higher proportions of marine fish (versus freshwater), macrocarnivores and planktivores (versus omnivores, herbivores and detritivores) and larger fish, with greater maximum depth of distribution and longer lifespan. The observed trait patterns and trait–environment relationships are likely generated by multiple causal processes linked to physiological constraints due to temperature and salinity, size‐dependent biotic interactions, as well as habitat availability and connectivity. Biogeographical context and environmental conditions drive species richness and composition, and present results show that they also drive assemblage traits. The observed trait patterns and trait–environment relationships suggest that assemblage composition is determined by the functional role of species within ecosystems. Conservation strategies should be coordinated globally and ensure protection of an array of estuaries that differ in ecosystem features, even if some of those estuaries do not support high species richness.